THE TASALUH, TANAZUL, AND TAKHĀRUJ MODELS IN THE INHERITANCE PRACTICES OF MADURESE CLERICAL FAMILIES IN MADURA - A Mufti Khazin; Ahmad Musadad; Tri Pujiati; Ifa Mutitul Choiroh; Moh. Hatta; Baihaqi Baihaqi (Universitas Nurul Jadid, 2026)
This study examines the implementation of tasāluh, tanāzul, and takhāruj in inheritance settlement within the family of the late Kiai Haji AMM in Panaan Village, Palengaan, Pamekasan, Madura. The research addresses a theoretical tension between the textual-mathematical normativity of faraid and socio-cultural realities that prioritize deliberation and familial harmony. Employing a qualitative case study design within a socio-legal framework, the study integrates in-depth interviews, participant observation, inheritance agreement documentation, and analysis of classical Islamic inheritance jurisprudence alongside maqāṣid al-sharī‘ah theory. The findings demonstrate that faraid remains the acknowledged normative baseline; however, its application is mediated through tasāluh grounded in mutual consent (‘an tarāḍin). Tanāzul and takhāruj operate as flexible redistributive instruments that are jurisprudentially valid and socially adaptive. From a maqāṣid perspective, the practice safeguards not only ḥifẓ al-māl (protection of property) but also ḥifẓ al-‘ird and ḥifẓ al-ukhuwwah (protection of dignity and fraternity), thereby fostering substantive justice and preventing intra-family conflict. The study formulates a “Consensual-Religious Inheritance Model of Madura,” integrating textual normativity, moral authority of religious leaders, and relational justice. These findings contribute to strengthening mediation-based inheritance mechanisms within Indonesian Islamic family law and advancing contemporary discourse on living fiqh grounded in local socio-religious wisdom.